Kołowo-Symetryczne Nieliniowe Zagadnienia Statyki Płyt Siatkowych - Klemm, P.; Woźniak, C. (Engineering Transactions, 1969)
The subject of the paper is the circular symmetrical problem of the postcritical deflections of elastic plates. Following some papers a fundamental set of equation of the applied theory has been used to obtain the fundamental set of equation linear mesh plates has been given. This set has been used of the circular-symmetrical problem. It has been assumed that a mesh plate is orthotropic and the main directions of the orthotropy coincide with the parametric lines of polar system of coordination. The fundamental sets of equations consists of equations for the stress functions Φ(e), deflection functions u(e), moment tensions me (e) and rotations ve (e) and ye(e). Some examples has been presented for the solution of circular perforated plates and ring grids loaded radially. The effect of initial deflection of the mesh plate has been taken into account.